Analisis Pengaruh Leverage, Profitabilitas, Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Pada Perusahaan Sektor Food And Beverage Di BEI Tahun 2020-2022 - Tri Irawati; Erna Chotidjah Suhatmi; Suhesti Ningsih (ITB AAS INDONESIA, 2023)
In fact, companies engaged in the food and beverage sector are not dependent on current economic conditions. This sub-sector is able to run stably and survive in any economic conditions. Companies engaged in the food and beverage sector must also be required to be competitive and able to adapt to the times so that they need to maintain the company's performance at a good level. This study aims to determine the effect of leverage, profitability, and firm size on financial performance in companies in the food and beverage sector. Analytical descriptive method is used in this research. The data used in this research is secondary data for 2020-2022 sourced from the Indonesian Stock Exchange. The data used are 26 food and beverage companies. The data analysis used was multiple linear regression with Eviews 10 software. Based on the results of the study, it was found that partially leverage and firm size had an effect on the performance of food and beverage companies as indicated by the probability value of the t test less than the alpha value of 1%, namely 0.003 and 0.004 . Simultaneously or jointly the leverage, firm size and profitability variables affect the performance of food and beverage companies as shown in the F test probability value of less than 5% alpha of 0.001.